Transphobic discourse and moral panic convergence: a content analysis of my hate mail - Walker, Allyn (Criminology, 2023)
Recently, new social anxieties about transgender people have begun to emerge, framed as an issue of "grooming"—a term typically used in the context of child sexual abuse. In this way, moral panic about transgender people seems to be merging with oft-repeated social fears about pedophilia, resulting not only in policies criminalizing trans people and their allies but also in escalating hatred and threats toward trans-affirming educators. This pattern requires further inquiry. As a trans academic who has been at the center of moral panic, my own hate mail can provide material for this exploration. I conducted a content analysis of 231 letters and e-mails sent to me containing messages of hate, to answer the following research questions: What beliefs and understandings did my correspondents indicate having about me and my research? To what extent did my correspondents’ beliefs and understandings about me reflect intersecting contemporary moral panics around trans and queer people, pedophilia, and educators? What stated or implied goals did my correspondents aim to achieve by writing to me? The findings of this study can add to understanding of how moral panics can converge, and the consequences of their convergence for marginalized groups in academia and beyond.